2013
DOI: 10.1002/cnm.2601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on patient specific abdominal aortic aneurysm flow topology and mixing

Abstract: SUMMARY Computational fluid dynamics modeling was used to investigate changes in blood transport topology between rest and exercise conditions in five patient-specific abdominal aortic aneurysm models. Magnetic resonance imaging was used to provide the vascular anatomy and necessary boundary conditions for simulating blood velocity and pressure fields inside each model. Finite-time Lyapunov exponent fields, and associated Lagrangian coherent structures, were computed from blood velocity data, and used to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…However, this quasi-steady behavior can break down if the Reynolds and Womersley numbers are sufficiently increased. For example, exercise in AAA patients creates a more complex flow field [2], with higher WSS values [33]. A preliminary investigation of our methods on AAA exercise data showed that the WSS LCS can slightly fluctuate around the stable/unstable manifolds of TAWSS and demonstrate some time dependence behavior (results not shown).…”
Section: P 10mentioning
confidence: 90%
“…However, this quasi-steady behavior can break down if the Reynolds and Womersley numbers are sufficiently increased. For example, exercise in AAA patients creates a more complex flow field [2], with higher WSS values [33]. A preliminary investigation of our methods on AAA exercise data showed that the WSS LCS can slightly fluctuate around the stable/unstable manifolds of TAWSS and demonstrate some time dependence behavior (results not shown).…”
Section: P 10mentioning
confidence: 90%
“…While the in vivo profile at the supraceliac aorta likely deviates from a Womerseley profile, imposing the profile at the supraceliac level ensures sufficient length for the flow to develop so that flow features at the infrarenal segment are not sensitive to the profile at the supraceliac level (4,39).…”
Section: Methodsmentioning
confidence: 99%
“…Degradation of the aortic wall, inflammation with immune responses, and biochemical wall stress are mechanisms that promote AAA initiation, influenced by molecular genetics (1). After the irreversible process of aneurysm formation, the dilated vessel creates an environment with complex blood flow and wall shear stress distribution (4,5,9,14,22,37,38), which is thought to perpetuate aneurysm progression.The presence of intraluminal thrombus (ILT) complicates AAA growth. ILT is fibrin structure compound of platelets, blood cells, blood proteins, and cellular debris (20).…”
mentioning
confidence: 99%
“…We have performed preliminary study on the effect of simulated exercise flow conditions (increased Reynolds and Womersley numbers, as modeled in Arzani et al (2014a)) on WSS LCS, and observed that the quasi-steady behavior of near wall transport can break down due to the higher WSS magnitudes. In addition, pulsatile blood flow may have some cycle to cycle variations due to transient effects from the fluid mechanics or physiology.…”
Section: Discussionmentioning
confidence: 99%